Sustainability Disclosure and Retention Ratio on Stock Returns: Firm Value Moderation in Indonesian Listed Banks - Dhiva Asmara Dwi Nanda; Frido Saritua Simatupang (Yayasan Sinergi Kawula Muda, 2026)
This study examines the effect of ESG performance, measured by the Refinitiv ESG Score, and Retention Ratio on Stock Return, with Firm Value as a moderating variable, in banking companies listed on the Indonesia Stock Exchange. The population of this study consists of all banking companies listed on the Indonesia Stock Exchange, while the sample includes six listed banks selected using purposive sampling based on data availability criteria. The observation period spans 2019–2023, resulting in 30 bank-year observations. This study employs multiple regression analysis and moderated regression analysis to investigate both the direct effects and the moderating effects among the variables.The results indicate that Refinitiv ESG Score has a negative and statistically significant effect on Stock Return. In contrast, Retention Ratio shows a positive but statistically insignificant effect on Stock Return. Furthermore, Firm Value, measured by Tobin’s Q, significantly moderates the relationship between Refinitiv ESG Score and Stock Return by weakening the effect. This finding suggests that higher firm value does not necessarily strengthen the market response to ESG performance. Meanwhile, Firm Value does not significantly moderate the relationship between Retention Ratio and Stock Return.Overall, the findings imply that ESG performance and dividend policy do not uniformly translate into higher Stock Return in the banking sector. Therefore, companies are encouraged to enhance their communication strategies to better convey the long-term value of ESG initiatives and retained earnings to investors, particularly in the context of firm valuation.